2015
DOI: 10.1002/2014gl062015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arctic haze on surface cloud radiative forcing

Abstract: From 4 years of observations from Barrow, Alaska, it is shown that the cloud radiative impact on the surface is a net warming effect between October and May and a net cooling in summer. During episodes of high surface haze aerosol concentrations and cloudy skies, both the net warming and net cooling are amplified, ranging from +12.2 Wm À2 in February to À11.8 Wm À2 in August. In liquid clouds, approximately 50%-70% of this change is caused by changes in cloud particle effective radius, with the remainder being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
114
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 182 publications
(124 citation statements)
references
References 52 publications
7
114
0
Order By: Relevance
“…For present-day insolation (green line in Fig. 6c), the model CRF is 240 W m 22 at low elevations, comparing well with other studies on CRF in the Arctic (Zhao and Garrett 2015). The figure shows only four of the runs because interannual variation in CRF for the warm and cold simulations is too large to allow us to deduce any clear temperature dependence.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…For present-day insolation (green line in Fig. 6c), the model CRF is 240 W m 22 at low elevations, comparing well with other studies on CRF in the Arctic (Zhao and Garrett 2015). The figure shows only four of the runs because interannual variation in CRF for the warm and cold simulations is too large to allow us to deduce any clear temperature dependence.…”
supporting
confidence: 84%
“…From measurements and modeling (Weller 1972;Shupe and Intrieri 2004;Zhang et al 1996), we know that CRF has a dominant role in the mass balance in the Arctic. The CRF can range from ;40 to 275 W m 22 (Zhao and Garrett 2015), which translates to a positive CRF (warming) in the winter months and cooling during the summer of about 250 W m…”
mentioning
confidence: 99%
“…The direct effect of aerosol on radiation refers to the scattering and absorption of the solar and longwave radiation by aerosol (Charlson et al, 1992;Koren et al, 2004;Lohmann and Feichter, 2005;Qian et al, 2007;Li et al, 2011;Huang et al, 2014;Yang et al, 2016) and the indirect effect of aerosol on radiation is associated with changes in the cloud macro-and micro-physical properties caused by aerosol which can serve as cloud condensation nuclei or ice nuclei (Twomey, 1977;Albrecht, 1989;Kaufman and Fraser, 1997;Feingold, 2003;Garrett et al, 2004;Gar-rett and Zhao, 2006;Zhao et al, 2012;Hoose and Möhler, 2012;Liu et al, 2012;Zhao and Garrett, 2015). The radiative effect of aerosol is relatively large due to increased emissions of pollution in East Asia (Wang et al, 2010a;Zhuang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On the other, polluted clouds can reflect more sunlight, leading to a cooling effect (Lubin and Vogelmann, 2007). Zhao and Garrett (2015) found that seasonal changes in surface radiation associated with haze pollution range from +12.2 W m −2 in February to −11.8 W m −2 in August. Annually averaged, the longwave warming and shortwave cooling nearly compensate, although the seasonal timing of the forcings may have implications for rates of sea ice melt (Belchansky et al, 2004;Markus et al, 2009).…”
Section: Introductionmentioning
confidence: 99%